Toward crop–livestock integration: a comprehensive framework for cropping system adaptation assessment to mitigate forage shortage - Dan Liu; Jianjun Jin; Xin Qiu; Rui He; Linna Li; Jie Yang (Environment, Development and Sustainability, 2024)

An automatic methodology for lithology identification in a tight sandstone reservoir using a bidirectional long short-term memory network combined with Borderline-SMOTE - Chong Hu; Rui Deng; Xueyi Hu; Mengcheng He; Hui Zhao; Xuemeng Jiang (Acta Geophysica, 2024)

Egg production monitoring in commercial laying cages via the StrongSort-EGG tracking-by-detection model - Rui Wu; Pengguang He; Yefan He; Jun Dou; Mengzui Di; Shupeng He; Khawar Hayat; Yi Zhou; Lin Yu; Jinming Pan; Hongjian Lin (Computers and Electronics in Agriculture, 2024)

Improving the affordability and reducing greenhouse gas emissions of the EAT-Lancet diet in China - Meng Li; Yanan Wang; Shunan Zhao; Wei Chen; Yu Liu; Heran Zheng; Zhongxiao Sun; Pan He; Rui Li; Sun Zhang; Peixue Xing; Qiao Li (Sustainable Production and Consumption, 2024)

High-temperature anaerobic calcination for stabilizing environmentally stressful elements in phosphoric acid production by-products - Minjie He; Changyi He; Guangfei Qu; Rui Xu (Sustainable Chemistry and Pharmacy, 2024)

Response of soil carbon and nitrogen stocks to irrigation - A global meta-analysis - Weihao Sun; Zhibin He; Dengke Ma; Bing Liu; Rui Li; Shuai Wang; Arash Malekian (Science of The Total Environment, 2024)

Surface coal mining in drylands: A multiscale comparison of spatiotemporal patterns and environmental impacts between Inner Mongolia and Mongolia - Qun Ma; Xuening Fang; Lingqiang Kong; Rui Zhou; Chunyang He; Xiaoji Zeng; Jianguo Wu (Science of The Total Environment, 2024)

Effective identification of debris-covered glaciers in Western China using multiple machine-learning algorithms - Rui He; Donghui Shangguan; Qiudong Zhao; Shiqiang Zhang; Zizhen Jin; Yan Qin; Yaping Chang (Science of The Total Environment, 2024)

Neolithization of Dawenkou culture in the lower Yellow River involved the demic diffusion from the Central Plain - Fen Wang; Rui Wang; Hao Ma; Wen Zeng; Yongsheng Zhao; Hao Wu; Zhongming Tang; Haifeng He; Hui Fang; Chuan-Chao Wang (Science Bulletin, 2024)

Higher water content observed in smaller size fraction of Chang'e-5 lunar regolith samples - Honglei Lin; Rui Xu; Shuai Li; Rui Chang; Hejiu Hui; Yang Liu; Hengci Tian; Kai Fan; Zhiping He; Huaiyu He; Wei Yang; Yangting Lin; et al. (Science Bulletin, 2024)

A ship motion forecasting approach based on Fourier transform, regularized Bi-LSTM and chaotic quantum adaptive WOA - Ming-Wei Li; Rui-Zhe Xu; Jing Geng; Wei-Chiang Hong; He Li (Ocean Engineering, 2024)

Contractor-oriented optimization for wind farm maintenance decision-making considering partial monitoring information and degraded working efficiency - Yifei Wang; Rui He; Zhigang Tian; Yinuo Chen (Ocean Engineering, 2024)

Influence of edge scour on lateral responses of monopiles with precast microbial reinforcement - Siyuan He; Jinhai Zheng; Rui He; Seyed Mohammad Javad Hosseini; Tao Zhu; Liang Cheng; Zhen Guo (Ocean Engineering, 2024)

Holocene paleoenvironment of the Nihewan Basin, China, inferred from high-resolution luminescence dating and a multiproxy analysis of gully sediments - Qing-Hao Ma; Yu-Jie Guo; Hua-Rui Lei; Yu-He Shen; Jia-Jing Wang; Ya Liu; Zhen-Yu Zhou; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Contrasting fracturing and cementation timings during shale gas accumulation and preservation: An example from the Wufeng-Longmaxi shales in the Fuling shale gas field, Sichuan Basin, China - Tao Luo; Xiaowen Guo; Zhiliang He; Jian-xin Zhao; Ze Tao; Tian Dong; Rui Yang; Junlin Chen (Marine and Petroleum Geology, 2024)

Benching of a real Chinese salt lake environment to achieve lithium ion concentration and osmotic power generation through ionic equilibrium concentration in the forward osmosis process - Jiaqi Wang; Yanwei Chen; Lei Wang; Miaolu He; Xudong Wang; Yongtao Lv; Jin Wang; Rui Miao (Journal of Water Process Engineering, 2024)

Effects of tauroursodeoxycholate on arsenic-induced hepatic injury in mice: A comparative transcriptomic analysis - Xiujuan Zheng; Jianbin Cao; He Wang; Lele Liu; Baiming Jin; Hua Zhang; Mingqi Li; Shijing Nian; Haonan Li; Rui He; Ningning Wang; Xuying Li; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Ultrabright silicon nanoparticles combined with o-phenylenediamine for ratiometric fluorescence and smartphone imaging dual-mode detection of nitrite - Wen-Jie Gao; Ming-Yue Tian; Xing-Hui Ren; Hao-Rui Zhang; Xi-Wen He; Wen-You Li; Yu-Kui Zhang (Journal of Hazardous Materials, 2024)

ABA-regulated MAPK signaling pathway promotes hormesis in sugar beet under cadmium exposure - Xiaoxin Zhao; Shuoqi Huang; Qi Yao; Rui He; Hao Wang; Zhaodan Xu; Wang Xing; Dali Liu (Journal of Hazardous Materials, 2024)

Seismic Reflection Imaging Reveals Relict Subduction Zone of the Paleo-Pacific Plate in the Northeastern South China Sea - Zongdong Pan; Shaoping Lu; Hongfang Gao; Lun Li; Han Chen; Rui Gao; Qing He (Journal of Asian Earth Sciences, 2024)

Mechanisms of manganese-tolerant Bacillus brevis MM2 mediated oxytetracycline biodegradation process - Zhiyan Li; Jin Wang; Rui Deng; Liu Azuan; Mingzhu Chen; Xiao He; Zhengbo Yue (Environmental Pollution, 2024)

Development of self-centering and energy-dissipating dual-stage reinforced concrete rocking column-base system - Genqi Xiao; Haishen Wang; Peng Pan; Hengyi Pan; Rui He; Guyu Tian (Engineering Structures, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Integrative experimental and computational analysis of the impact of KGM's polymerization degree on wheat starch's pasting and retrogradation characteristics - Yi Zhao; Juan Wang; Rui He; Yuanyuan Ren; Jin Fu; Yunjun Zeng; Kangyi Zhang; Geng Zhong (Carbohydrate Polymers, 2024)

Model test of in-situ remediation for heavy metal-contaminated clayey soil by artificial freezing and shaft washing - Jun Zhang; Wenjun Nie; Mintae Kim; Xianghong He; Dahu Rui; Weidong Pan (Cold Regions Science and Technology, 2024)

Activated carbon fiber loaded nano zero-valent iron for Microcystis aeruginosa removal: Performance and mechanisms - Guoming Zeng; Dong Liang; Xuanhao Fan; Yu He; Rui Zhang; Xiaoling Lei; Haoxuan Wei; Da Sun (Bioresource Technology, 2024)

Nischarin inhibits the epithelial-mesenchymal transition process and angiogenesis in breast cancer cells by inactivating FAK/ERK signaling pathway via EGF like repeats and discoidin domains 3 - Ruzhen Zheng; Yibo He; Lingrong Yang; Yidan Chen; Rui Wang; Shangnao Xie (Molecular Biology Reports, 2024)

CircCOX6A1 suppresses osteogenic differentiation and aggravates osteoporosis via miR-512-3p/DYRK2 axis - Dingwen He; Sikuan Zheng; Jian Cao; Jianjian Deng; Rui Ding; Yanjie Xu; Xigao Cheng (Molecular Biology Reports, 2024)

EGR1 transcriptionally regulates SVEP1 to promote proliferation and migration in human coronary artery smooth muscle cells - Qiang Tian; Jia-He Chen; Yi Ding; Xin-Yu Wang; Jia-Yun Qiu; Qian Cao; Li-Li Zhuang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2024)

Study of the effect of keap1 on oxidative stress in human umbilical cord mesenchymal stem cells - Hongrong Deng; Yunxia Chen; Huiwen Liu; Li Wang; Hao Xu; Bin Tan; Qin Yi; Rui Wang; Bolin He; Jie Tian; Jing Zhu (Molecular Biology Reports, 2024)
Background HucMSCs had shown promising efficacy in treating childhood diseases, but oxidative stress induced by the poor microenvironment at the site of damage resulted in low cell survival after transplantation, thus preventing the cells from maximizing therapeutic efficacy. Therefore, this study aimed to investigate the role and mechanism of keap1 in oxidative stress injury of human umbilical cord mesenchymal stem cells (hucMSCs), and to provide theoretical support for improving the efficacy of stem cell therapy. Methods The hucMSCs were treated with hypoxic low-sugar-free serum (GSDH) to mimic the damaged site microenvironment after implantation. Adenoviral overexpression of keap1 gene of hucMSCs was performed in vitro, and cell proliferation ability was detected by CCK8 assay, crystal violet staining assay, and cell cycle assay. Cellular redox level was assessed by Amplex Red, MDA, and GSH/GSSG kit. Mitochondrial morphology was evaluated by mitotracker Red staining. ATP production was estimated by ATP detection kit. The mRNA and protein expression levels were tested by western blotting and RT-qPCR. Results GSDH treatment substantially upregulated keap1 expression. Subsequently, we found that overexpression of keap1 notably inhibited cell proliferation and caused cells to stagnate in G1 phase. At the same time, overexpression of keap1 induced the production of large amounts of H 2 O 2 and the accumulation of MDA, but suppressed the GSH/GSSG ratio and the expression of antioxidant proteins NQO1 and SOD1, which caused oxidative stress damage. Overexpression of keap1 induced cells to produce a large number of dysfunctional mitochondria resulting in reduced ATP production. Moreover, Overexpression of keap1 significantly decreased the IKKβ protein level, while upregulating IkB mRNA levels and downregulating P50 mRNA levels. Conclusions Overexpression of keap1 may induce oxidative stress injury in hucMSCs by down-regulating IKKβ expression and inhibiting NF-κB pathway activation. This implies the importance of keap1 in hucMSCs and it may be a potential gene for genetic modification of hucMSCs.

MiR-3571 modulates traumatic brain injury by regulating the PI3K/AKT signaling pathway via Fbxo31 - Yang Zhang; Zongying He; Qiongfang Hu; Huali Liu; Rongai Wen; Na Ru; Jinghua Yu; Shaokun Lv; Rui Tao (Cell Biochemistry and Biophysics, 2024)

Synthesis of Fe-ZSM-5 zeolite from high iron-containing palygorskite with peroxidase-like catalytic performance - Fengya Ran; Meng He; Shiyong Sun; Rui Lv; Sen Lin; Ke Wang; Yevgeny Aleksandrovich Golubev; Olga Borisovna Kotova; Elena Leonidovna Kotova (Applied Clay Science, 2024)

An autonomous ore packing system through deep reinforcement learning - He Ren; Rui Zhong (Advances in Space Research, 2024)

Optimization of Preparation Technology for PET-Based Carbon Dots by Response Surface Method and Its Application - Chaohui Ma; Gaoling Jin; Puzhen He; Chuanjiang Tang; Linhan Bing; Botong Liu; Hanjiang Huang; Yu Fan; Rui Wang; Jianfei Wei (Journal of Fluorescence, 2024)

An Innovative Online Adaptive High-Efficiency Controller for Micro Gas Turbine: Design and Simulation Validation - Rui Yang; Yongbao Liu; Xing He; Zhimeng Liu (Journal of Marine Science and Engineering, 2024)
In this article, an innovative online adaptive high-efficiency control strategy is proposed to improve the power generation efficiency of a marine micro gas turbine under partial load. Firstly, a mathematical model of the micro-gas turbine is established, and a control strategy consisting of an on-board prediction model and an online update model is proposed. To evaluate the performance changes of the gas turbine, we applied deep learning techniques to enhance the extreme learning machine (ELM) algorithm, resulting in the development of a high-precision, high-real-time deep extreme learning machine (DL_ELM) prediction model. This model effectively monitors changes in the gas turbine’s performance. Furthermore, an online time-series deep extreme learning machine with a dynamic forgetting factor (DFF_DL_OSELM) model is designed to achieve the real-time tracking of performance variations. When the DL_ELM model detects a gas turbine’s performance change, a particle swarm optimization (PSO) algorithm is employed to iteratively calculate the DFF_DL_OSELM model, determining the optimal speed control scheme to ensure the gas turbine operates at maximum efficiency. To validate the superiority of the proposed control strategy, a comparison is made with traditional high-efficiency control strategies based on polynomial fitting and BP neural networks. The results demonstrate that although all three strategies can achieve efficient operation under constant conditions, traditional strategies fail to identify and adjust to performance changes in real time, leading to decreased control performance and potential engine damage as engine characteristics degrade. In contrast, the proposed online adaptive control strategy dynamically adjusts the speed control plan based on performance degradation, ensuring that the gas turbine operates efficiently while keeping the turbine inlet and exhaust temperatures within safe limits.

Sappanone A ameliorates acute lung injury through inhibiting the activation of the NF-κB signaling pathway - Jing Du; Piao Zhou; Xin Zhao; Yu-Ting He; Cheng-Shi He; Rui-Yu Wang (Toxicology and Applied Pharmacology, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Effect of urban structure on land surface temperature around elementary schools in Hangzhou based on local climate zones - Xincheng He; Weijun Gao; Rui Wang (Sustainable Cities and Society, 2024)

Long-term effects of conventional cultivation on soil cation exchange capacity and base saturation in an arid desert region - Dengke Ma; Zhibin He; Wenzhi Zhao; Rui Li; Weihao Sun; Wen Wang; Pengfei Lin; Lemin Wei; Wenliang Ju (Science of The Total Environment, 2024)

KMT2D deficiency leads to cellular developmental disorders and enhancer dysregulation in neural-crest-containing brain organoids - Ziyun Shan; Yingying Zhao; Xiuyu Chen; Guodong Zhan; Junju Huang; Xuejie Yang; Chongshen Xu; Ning Guo; Zhi Xiong; Fang Wu; Yujian Liu; He Liu; et al. (Science Bulletin, 2024)

Peering through the hedge: Multiple datasets yield insights into the phylogenetic relationships and incongruences in the tribe Lilieae (Liliaceae) - Deng-Feng Xie; Juan Li; Jia-Hui Sun; Rui-Yu Cheng; Yuan Wang; Bo-Ni Song; Xing-Jin He; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2024)

All-electrochemical-prepared, efficient and robust superhydrophilic/underwater superoleophobic meshes for synchronously achieving oil-water separation and water-soluble pollutant photodegradation - Jiali Yang; Tingting He; Xinyi Li; Rui Wang; Yang Zhao; Huan Wang (Journal of Water Process Engineering, 2024)

Granular insights into occupant behaviours and CO2 emissions in the UK - Ruiming Zhang; Tongyu Zhou; Rui Jing; Hua Cai; Tao Lin; Kai Wang; Huanye He; Guoqin Zhang; Xian Wu; Hong Ye (Journal of Cleaner Production, 2024)

Unveiling the impact of low-molecular-weight organic acids on enrofloxacin sorption in North China agricultural soil: Insights and implications - Yufeng Jiang; Jiali Wu; Zhewei Liu; Rui He; Xiaozhen Zhang; Kui Huang; Yingqin Wu (Journal of Environmental Management, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Combination of plant species and water depth enhance soil quality in near-natural restoration of reclaimed wetland - Tao Yang; Jing Jiang; Fengxue Shi; Rui Cai; Haibo Jiang; Lianxi Sheng; Chunguang He (Ecological Engineering, 2024)

Research progress on P2-type layered oxide cathode materials for sodium-ion batteries - Chen Wu; Yuxing Xu; Jiechen Song; Ying Hou; Shiyang Jiang; Rui He; Aijia Wei; Qiangqiang Tan (Chemical Engineering Journal, 2024)

Precise regulation of layered-to-rock structure of spent Li-ion cathodes achieving ultrahigh lithium recovery rate - Xue Bai; Yanzhi Sun; Rui He; Zhenfa Liu; Junqing Pan (Chemical Engineering Journal, 2024)

Ultrathin PVP/ZnMoO4@PE separator for high-safety sodium-ion batteries - Siya Cheng; Qingwen He; Rui Deng; Zhi Zhang; Huanyi Liao; Yifan Zheng; Zhongxi Li; Jianing Lu; Yumeng Jiang; Yihua Gao (Chemical Engineering Journal, 2024)

Perovskite nanocrystals photo-initiated in situ encapsulation for optical tracking - Xiao’e Jia; Tongyu Shi; Qingyuan Zhang; Hao Huang; Paul K. Chu; Xue-Feng Yu; Rui He (Chemical Engineering Journal, 2024)

Formation of flake-like DAAF crystals with tunable size realized on a microfluidic platform for binder-free initiator explosives - Bo Yang; Shengshu Xi; Simin He; Jin Chen; Wei Cao; Rui Li; Rupeng Bu; Xiaona Huang; Jincan Zhu; Qi Wu; Weimiao Wang; Xiaodong Li; et al. (Chemical Engineering Journal, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Construction of ROS-balancing-engineered heterojunction photoswitch for achieving programmed inflammatory management and tissue regeneration - Bin Luo; Jing He; Jiahui Lei; Rui Wen; Xiaoqin Hu; Fang Lan; Yao Wu (Chemical Engineering Journal, 2024)

In-situ growth of Ni, Co-Prussian blue nanocubes on molten salt etched lamellar Ti3C2Tx/Ni for enhanced hybrid capacitive deionization - Wen Xi; Youfang Zhang; Jianing Hu; Zongchang Li; Rui Wang; Huanwen Wang; Yansheng Gong; Beibei He; Jun Jin (Chemical Engineering Journal, 2024)

Thermal comfort of healthcare facilities in China: A review - Rui Guan; Jun Lu; Zhen Peng; Siyu Ma; Wu Deng; Zhiang Zhang; Paolo Beccarelli; Tong He (Building and Environment, 2024)

Establishment of high temporal-spatial resolution anthropogenic emission inventory of air pollutants in 2017 for Macao, China - Yongfan Wu; Yan You; Zhongcai Wang; Andi Zhang; Yuanxi Gao; Shuai Wang; Yang Liu; Rui He; Zhijiong Huang; Shaojun Zhang (Atmospheric Environment, 2024)

Unveiling the evolutionary dynamics of microRNA-targeted plant laccase genes - Rui-Rui He; Meng-Qi Lei; Yan-Zhao Feng; Jiao Xue; Yu-Chan Zhang; Yue-Qin Chen; Yang Yu (Science China Life Sciences, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

Specific and Plastic: Chandelier Cell-to-Axon Initial Segment Connections in Shaping Functional Cortical Network - Yanqing Qi; Rui Zhao; Jifeng Tian; Jiangteng Lu; Miao He; Yilin Tai (Neuroscience Bulletin, 2024)
Axon initial segment (AIS) is the most excitable subcellular domain of a neuron for action potential initiation. AISs of cortical projection neurons (PNs) receive GABAergic synaptic inputs primarily from chandelier cells (ChCs), which are believed to regulate action potential generation and modulate neuronal excitability. As individual ChCs often innervate hundreds of PNs, they may alter the activity of PN ensembles and even impact the entire neural network. During postnatal development or in response to changes in network activity, the AISs and axo-axonic synapses undergo dynamic structural and functional changes that underlie the wiring, refinement, and adaptation of cortical microcircuits. Here we briefly introduce the history of ChCs and review recent research advances employing modern genetic and molecular tools. Special attention will be attributed to the plasticity of the AIS and the ChC-PN connections, which play a pivotal role in shaping the dynamic network under both physiological and pathological conditions.

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Study on the source identification and migration and transformation characteristics of heavy metal pollution in sediments of Chaohu Lake Tongyang River Basin - Zhenyu He; Yanjun Li; Bo Kang; Rui Li; Kun Chen; Jie Yang; Yuezan Tao (Environmental Monitoring and Assessment, 2024)

Exploring the sorption/desorption of nitenpyram in loess soils: implications for neonicotinoid fate and ecological risk assessment - Rui He; Yufeng Jiang; Zhewei Liu; Jiali Wu; Xiaozhen Zhang; Yingqin Wu (Environmental Geochemistry and Health, 2024)

Shifts in organic carbon protection mechanism in agricultural soils across climatic gradients - Chong Ma; Yinhang Xia; Yichao Rui; Wei Gao; Xun Duan; Hang Qiao; Xunyang He; Yajun Hu; Daoyou Huang; Jinshui Wu; Yirong Su; Georg Guggenberger; et al. (Agriculture, Ecosystems & Environment, 2024)

Prolonged exposure to NaAsO2 induces thyroid dysfunction and inflammatory injury in Sprague‒Dawley rats, involvement of NLRP3 inflammasome‒mediated pyroptosis - Lili Fan; Qian Song; Ying Jin; Rui He; Heng Diao; Peng Luo; Dapeng Wang (Archives of Toxicology, 2024)

Assessment of brittle failure in deep tunnels via true triaxial compression - Ben-Guo He; Hong-Pu Li; Xiang-Rui Meng; Si-Yuan Dou; Shengcun Yan; Tao Chen (Tunnelling and Underground Space Technology, 2024)

Rainfall runoff response characteristics of typical urban roads based on laboratory tests - Haiqi He; Rui Li; Lei Lyu; Yi Wu; Jean-Pascal Bilodeau; Yong Wen; Zikai Xu; Jianzhong Pei (Transportation Research Part D: Transport and Environment, 2024)

Internal solitary wave-induced soil responses and its effects on seabed instability in the South China Sea - Linlong Tong; Jisheng Zhang; Ning Chen; Xiangfeng Lin; Rui He; Lei Sun (Ocean Engineering, 2024)

Investigation on a sustainable magnesium phosphate cement (MPC) with recycled waste MPC powders - Heping Qiu; Jincheng Yu; Huaxin Chen; Dongliang Kuang; Rui He (Journal of Environmental Chemical Engineering, 2024)

Disinfection of bacteria and viruses under near infrared light by tunable self-assembled nanomaterial NH2-MIL-101-xAu based on photothermal and photodynamic mechanisms - Nian Li; Zi-jian He; Jia-min Gan; Xing-rui Qi; Shu-nuo Bian; Yu-fang Chen; Bo Liu; Hua-jie Lai; Tao Jin (Journal of Environmental Chemical Engineering, 2024)

Research progress and prospect of covalent organic frameworks (COFs) and composites: From synthesis to application in water contaminants - Rui Li; Fengfei Sun; Zhen Liu; Yuwei Shi; Sizhe He; Junfeng Chen (Journal of Environmental Chemical Engineering, 2024)

Enhancing volatile fatty acid production from food waste by H2O2-moderate temperature thermal pretreatment: Treating waste with waste in coal mining areas - Rui Miao; Minghui Zhang; Jialin Wan; Zhangwei He; Jinwen Wang; Yongtao Lv; Danxi Huang; Lei Wang (Journal of Environmental Chemical Engineering, 2024)

Self-cleaning of metal-organic framework membranes achieved by photocatalytic ZIFs for dye and antibiotic separation - Jie He; Rui Zhang; Dong Chen; Ziyin Chen; Jiacheng Jiang; Maoqing Xu; Yujie Liu; Zixi Li; Lin Peng; Yong Shu; Luming Jiang; Guixiang Zhao (Journal of Environmental Chemical Engineering, 2024)

In-orbit detection of the spectral smile for the Mars Mineral Spectrometer - Bing Wu; Rui Xu; Chengyu Liu; Zhiping He (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Enhancement of bio-jet fuel production from corncob by iron ion-catalyzed hydrogen peroxide pretreatment - Rui Zhang; Yuting He; Rui Zhu; Can Zhu; Yu Jiang; Yuming Ni; Minghui Fan; Quanxin Li (Fuel, 2024)

In vitro digestion and functional properties of bovine β-casein: A comparison between adults and infants - Xiaoqian Chen; Rui Fan; Xinyu Wang; Lina Zhang; Caiyun Wang; Zhanqun Hou; Chun Li; Libo Liu; Jian He (Food Research International, 2024)

Characterization of selenium-containing broccoli (Brassica oleracea L. var. italica planch) proteins and evaluation of antioxidant activity by electron spin resonance - Jinjing Yin; Wei Liu; Muci Wu; Ming Chen; Xun Pei; Yuzhen He; Fangxiong Shen; Rui Zhang; Jingren He (Food Chemistry, 2024)

Biosynthesis pathway of flavor compound 3-methylbutanal derived from leucine by Lactococcus lactis 517: From a transcriptomics perspective - Lei Chen; Rui Liu; Chenxiang He; Mangang Wu; Qingfeng Ge; Hai Yu (Food Bioscience, 2024)

Association between heatwaves and risk and economic burden of injury related hospitalizations in China - Cheng Zhao; Yushu Huang; Yibin Cheng; Rui Zhang; Yu Wang; Shilu Tong; Jiang He; Jia Guo; Fan Xia; Yonghong Li; Xiaoyuan Yao (Environmental Research, 2024)

Use of modified poly-epoxysuccinic acid as an efficient scale inhibitor to control CaSO4 scaling in NF processes: Performance and mechanisms - Xinyuan Yi; Shumin Yang; Xin He; Zhiwei Wang; Min Rui; Yulin Tang (Desalination, 2024)

Multifunctional molecular bridge enabled interface passivation and strain release for stable and efficient all-inorganic perovskite solar cells - Zhiwei Ma; Benlin He; Rui Tui; Xinyi Zhang; Qihang Cheng; Changqing Liu; Haiyan Chen; Jialong Duan; Qunwei Tang (Chemical Engineering Journal, 2024)

Immune checkpoint-regulatable hydrogel-immobilized nanotherapeutics for post-surgical treatment of osteosarcoma - Da-Wang Zhao; Zhiliang Gao; Meng Si; Rui Hu; Xue Ma; Kaiwen Liu; Yixiang Zhao; Qiting He; Xiangzhen Kong; Chunwang Jia; Haoxin Zhai; Yuanqiang Zhang; et al. (Chemical Engineering Journal, 2024)

Incorporating hydrogen bonding networks in microporous polymer membranes for high-flux hydrocarbon separation - Yanxiong Ren; Jingqi Fu; Rui Ding; Yunshu Li; Xu Liang; Zheyuan Guo; Jianyu Wang; Ziting Zhu; Hong Wu; Guangwei He; Zhongyi Jiang (Chemical Engineering Journal, 2024)

Spatial control of nanoreactions on cellulose nanofibers using drop evaporation - Rui Ding; Min Zhang; Lujia Xuan; Zhengyuan Ma; Yixiao Qu; Zheng Liu; Hui He; Ruoyang Chen (Chemical Engineering Journal, 2024)

Dialdehyde starch cross-linked aminated gelatin sponges with excellent hemostatic performance and biocompatibility - Yu-He Zhu; Chen-Yu Zhou; Xu Peng; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Xiao-Jie Ju; Liang-Yin Chu (Carbohydrate Polymers, 2024)

Investigating thermal exposure during daily walking through a human-scale approach: An analysis of a hot summer in Wuhan - Jiwei Xu; Xinkun Xu; Zimeng Wang; Huiting Chen; Qiran Ren; He Huang; Yao Cui; Rui An; Yaolin Liu (Building and Environment, 2024)

WNT2B high‑expressed fibroblasts induce the fibrosis of IBD by promoting NK cells secreting IL-33 - Yanling Cheng; Shuzhe Xiao; Lin Lan; Danqiong Liu; Rui Tang; Jianbiao Gu; Li Ma; Zhihua He; Xirong Chen; Lanlan Geng; Peiyu Chen; Huiwen Li; et al. (Journal of Molecular Medicine, 2024)

Soil urease functional stability to Hg pollution: An ecotoxicological perspective - Hui Huang; Haixia Tian; Yan Li; Ziquan Wang; Tiantian Yang; Rui Qian; Mallavarapu Megharaj; Wenxiang He (Ecotoxicology, 2024)

TNF-α and RPLP0 drive the apoptosis of endothelial cells and increase susceptibility to high-altitude pulmonary edema - Yi-Ling Ge; Pei-Jie Li; Ying-Rui Bu; Bin Zhang; Jin Xu; Si-Yuan He; Qing-Lin Cao; Yun-Gang Bai; Jin Ma; Lin Zhang; Jie Zhou; Man-Jiang Xie (Apoptosis, 2024)
High-altitude pulmonary edema (HAPE) is a fatal threat for sojourners who ascend rapidly without sufficient acclimatization. Acclimatized sojourners and adapted natives are both insensitive to HAPE but have different physiological traits and molecular bases. In this study, based on GSE52209, the gene expression profiles of HAPE patients were compared with those of acclimatized sojourners and adapted natives, with the common and divergent differentially expressed genes (DEGs) and their hub genes identified, respectively. Bioinformatic methodologies for functional enrichment analysis, immune infiltration, diagnostic model construction, competing endogenous RNA (ceRNA) analysis and drug prediction were performed to detect potential biological functions and molecular mechanisms. Next, an array of in vivo experiments in a HAPE rat model and in vitro experiments in HUVECs were conducted to verify the results of the bioinformatic analysis. The enriched pathways of DEGs and immune landscapes for HAPE were significantly different between sojourners and natives, and the common DEGs were enriched mainly in the pathways of development and immunity. Nomograms revealed that the upregulation of TNF-α and downregulation of RPLP0 exhibited high diagnostic efficiency for HAPE in both sojourners and natives, which was further validated in the HAPE rat model. The addition of TNF-α and RPLP0 knockdown activated apoptosis signaling in endothelial cells (ECs) and enhanced endothelial permeability. In conclusion, TNF-α and RPLP0 are shared biomarkers and molecular bases for HAPE susceptibility during the acclimatization/adaptation/maladaptation processes in sojourners and natives, inspiring new ideas for predicting and treating HAPE.

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Activation of peroxymonosulfate by β-FeOOH@Cia-MoS2 for enhancing degradation of tetracycline: Significant roles of surface functional groups and Fe/Mo redox reactions - Jingjing Wang; Fang He; Jieru Fang; Rui Yu; Zaiwen Jia; Haihong Zhou (Chemosphere, 2024)

Artificial humic acid produced from wet distillers grains in a microwave-assisted hydrothermal process: Physicochemical characteristics and stimulation to plant growth - Tianlong Lei; Jie Su; Luyi Chang; Rui He; Guangchun Shan; Xiaomei Jiang; Yunhui Lei; Xiaobo Guo (Chemosphere, 2024)

Water and fertilizer decision model for synergistic optimization of yield, quality and efficiency of cherry tomato based on combination evaluation - Rui Li; Jiaming Bai; Dayong Li; Xinru Ren; Daiwei He; Rongcheng Du; Ziqi Feng; Zhi Zhang (Computers and Electronics in Agriculture, 2024)

Megastigmane glycosides from the traditional Uighur medicine Cydonia oblonga Mill. - Shan-Shan Jiao; Rui-Feng Ding; Xin Yuan; Xiao-Ping He; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2024)

Influence of precast microbial reinforcement on lateral responses of monopiles - Tao Zhu; Rui He; Seyed Mohammad Javad Hosseini; Siyuan He; Liang Cheng; Yakun Guo; Zhen Guo (Ocean Engineering, 2024)

Construction of g-C3N4@Bi-MOF@BiOCl double Z-type heterojunctions for photodegradation of antibiotics under visible light irradiation: Mechanism, pathway, and toxicity assessment - Maoqin Xu; Rui Zhang; Jie He; Zixi Li; Yujie Liu; Dong Chen; Lin Peng; Yong Shu; Luming Jiang; Guixiang Zhao (Journal of Water Process Engineering, 2024)

Associations between multiple urinary metals and metabolic syndrome: Exploring the mediating role of liver function in Chinese community-dwelling elderly - Yuqing Dai; Siyu Duan; Rui Wang; Pei He; Zhongyuan Zhang; Meiyan Li; Zhuoheng Shen; Yue Chen; Yi Zhao; Huifang Yang; Xiaoyu Li; Rui Zhang; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

A novel OsGST gene encoding 9glutathione reductase negatively regulates cadmium accumulation in rice - Rui Guo; Su Li; Yong Qiang Gao; Jia Tong He; Hao Yu Wang; Jin Chen; Jiu Huang; Ren Fang Shen; Xiao Fang Zhu (Journal of Hazardous Materials, 2024)

Farmland’s silent threat: Comprehensive multimedia assessment of micropollutants through non-targeted screening and targeted analysis in agricultural systems - Yang Qiu; Lijun Liu; Caifei Xu; Bo Zhao; Hang Lin; He Liu; Weixuan Xian; Han Yang; Rui Wang; Xingjian Yang (Journal of Hazardous Materials, 2024)

Organophosphorus mineralizing-Streptomyces species underpins uranate immobilization and phosphorus availability in uranium tailings - Nan Hu; Fangfang Xiao; Dandan Zhang; Ruiwen Hu; Rui Xiong; Wenpan Lv; Zhaolan Yang; Wenfa Tan; Huang Yu; Dexin Ding; Qingyun Yan; Zhili He (Journal of Hazardous Materials, 2024)

TiO2 thermal stress deformation induced to promote photocatalytic CO2 reduction - Yixuan Shen; Kaifeng Gong; Le Chen; Jiafan Wang; Tao Wang; Yuan Gao; Jie Niu; Rui Zhu; Qizhen Liu; Jiang Wu; Ping He (Fuel, 2024)

Feasibility and safety of percutaneous intramyocardial septal cryoablation: A canine model with 6-month follow-up - Xiaonan Lu; Jing Li; David H. Hsi; Juan Zhang; Yupeng Han; Shengjun Ta; Jing Wang; Jin He; Jia Zhao; Chao Han; Lu Yao; Xumei Ou; et al. (Cryobiology, 2024)

An information quantity and machine learning integrated model for landslide susceptibility mapping in Jiuzhaigou, China - Yunjie Yang; Rui Zhang; Tianyu Wang; Anmengyun Liu; Yi He; Jichao Lv; Xu He; Wenfei Mao; Wei Xiang; Bo Zhang (Natural Hazards, 2024)

Adsorption/desorption of enrofloxacin in farmland soil as the effect of pH and coexisting ions: implications for enrofloxacin fate and risk in loess soil - Jiali Wu; Yufeng Jiang; Rui He; Zhewei Liu; Xiaozhen Zhang; Wenjing Wang; Weichen Kong; Gang Wang; Yingqin Wu (Environmental Geochemistry and Health, 2024)

Correction to: Calcitriol Inhibits NaAsO2 Triggered Hepatic Stellate Cells Activation and Extracellular Matrix Oversecretion by Activating Nrf2 Signaling Pathway Through Vitamin D Receptor - Dapeng Wang; Rui He; Qian Song; Heng Diao; Ying Jin; Aihua Zhang (Biological Trace Element Research, 2024)

Biocrusts enhance soil nitrogen mineralization and nitrification under experimental warming in a dryland ecosystem - Rui Hu; Hongxia Zhang; Jingyao Sun; Yafeng Zhang; Mingzhu He; Zhishan Zhang (Applied Soil Ecology, 2024)

Cyclic tensile stress promotes osteogenic differentiation via upregulation of Piezo1 in human dental follicle stem cells - Binqing Xie; Xianyi He; Ye Guo; Jie Shen; Binbin Yang; Rui Cai; Junliang Chen; Yun He (Human Cell, 2024)

Design and synthesis of ligustrazine derivatives as potential anti-Alzheimer’s agents - Xu-fei Chen; Shan-shan Li; Yu-jun Bai; Ze-feng Zhao; Ya-jun Bai; Gu Gong; Xi-rui He; Xiao-hui Zheng (Natural Product Research, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Heterologous expression and characterization of two delta glutathione S-transferases genes involved in imidacloprid metabolism in Grapholita molesta - Qin-Wei Pang; Wen-Jie He; Ming-Gao Li; Ming Wang; Xue-Yao Zhang; Li-Jun Zhang; Ling-Ling Gao; Rui-Yan Ma; Yan-Qiong Guo; Qin Yu (Chemosphere, 2024)

Stress mitigation mechanism of rice leaf microbiota amid atmospheric deposition of heavy metals - Hanbing Gao; Zhaohui Guo; Xiao He; Jinbo Yang; Li Jiang; Aiping Yang; Xiyuan Xiao; Rui Xu (Chemosphere, 2024)

Effect of tunnel ventilation on surrounding rock temperature field and heat regulating circle during construction phase - Ming-Rui Luo; Yu-Chun Tao; Zuo-Bing Yuan; Liang-Liang Tao; Chuan He; Yan-Ping Yuan; Xiao- Yu Tian; Yan-Hua Zeng (Tunnelling and Underground Space Technology, 2024)

Spatio-temporal patterns and population exposure risks of urban heat island in megacity Shanghai, China - Dan Liu; Rui Zhou; Qun Ma; Tianxing He; Xuening Fang; Lishan Xiao; Yina Hu; Jie Li; Lin Shao; Jun Gao (Sustainable Cities and Society, 2024)

In situ real-time pathway to study the polyethylene long-term degradation process by a marine fungus through confocal Raman quantitative imaging - Wanying He; Rui Liu; Fan Fei; Shichuan Xi; Zengfeng Du; Zhendong Luan; Chaomin Sun; Xin Zhang (Science of The Total Environment, 2024)

Karst carbon sink mechanism and its contribution to carbon neutralization under land- use management - Min Zhao; Dong Li; Zaihua Liu; Qian Bao; Fan Xia; Hao Yan; Bo Chen; Yundi Hu; Guanxia Cai; Rui Lang; Hang Li; Liangxing Shi; et al. (Science of The Total Environment, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

A novel semi-analytical model for laterally loaded piles - Rui He (Ocean Engineering, 2024)

Feasibility of nanofiltration process for efficient separation of gallic acid from the extract of black tea in aqueous solution - Yiwei Dong; Rui Zhao; Chunyan Xu; Jinxin Liu; Zhiguo Dong; Ziqi Chen; Jinfeng He; Chuanrun Li; Haiyang Yan; Li Sun (Journal of Water Process Engineering, 2024)

Utilizing oxygen-rich vacancies in Bi2O2CO3/ZnFe2O4 heterojunction photocatalytic materials for the efficient degradation of tetracycline hydrochloride in water - Hongqing He; Xianbin Li; Shunzhi Li; Weiwei Zhu; Rui Jiang; Zhiwei Zhai; Yang Cao (Journal of Water Process Engineering, 2024)

Spatial distribution of bioaerosols and evaluation of four ventilation method on controlling their diffusion in a typical enhanced biosafety level 2 laboratory - Zhijian Liu; Yongxin Wang; Chuan Jiang; Junzhou He; Rui Rong; Shiyue Li; Zhenyu Liang (Journal of Hazardous Materials, 2024)

Exploring the spatial patterns of landslide susceptibility assessment using interpretable Shapley method: Mechanisms of landslide formation in the Sichuan-Tibet region - Jichao Lv; Rui Zhang; Age Shama; Ruikai Hong; Xu He; Renzhe Wu; Xin Bao; Guoxiang Liu (Journal of Environmental Management, 2024)

A novel, green, and environmentally friendly PBS/nano-CaCO3 hybrid membrane - Ming Jing; Yanhong Ji; Liuchun Zheng; Xi Liu; Zunbo Han; Jiayi Cai; Rui Bai; Benqiao He (Journal of Environmental Chemical Engineering, 2024)

Preparation of ternary composite film TiO2/Fe2O3/Ti3C2 for photoelectrocatalytic degradation of organic pollutants and bacterial inactivation in water - Yanping Ma; Jialin Gu; Xinshang Li; Wenquan Zhou; He Wang; Rui Zhang; Jiangang Jiang (Journal of Environmental Chemical Engineering, 2024)

TA and CTAB treatment synergistically enhance activated sludge dewatering by lowering proteins and boosting Zeta potential - Weiliang Pan; Xun Zhang; Rui Deng; Li Gu; Xiuqing Tan; Shanji Yan; Ruihao Zhang; Qiang He (Journal of Environmental Chemical Engineering, 2024)

Two cytokine receptor family B (CRFB) members in orange-spotted grouper Epinephelus coioides, EcCRFB3 and EcCRFB4, negatively regulate interferon immune responses to assist nervous necrosis virus replication - Siyou Huang; Yiling Kang; Rui Zheng; Linwei Yang; Jie Gao; Wanting Tang; Jing Jiang; Jianguo He; Junfeng Xie (Fish & Shellfish Immunology, 2024)

Silica's silent threat: Contributing to skin fibrosis in systemic sclerosis by targeting the HDAC4/Smad2/3 pathway - Bingsi Tang; Yaqian Shi; Zhuotong Zeng; Xinglan He; Jiangfan Yu; Ke Chai; Jiani Liu; Licong Liu; Yi Zhan; Xiangning Qiu; Rui Tang; Yangfan Xiao; et al. (Environmental Pollution, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Rapid differential diagnosis of periprosthetic joint infection by microdroplet reaction on portable biochip and indicator - Zheng Liu; Jimei Chi; Zewei Lian; Yaqi Yang; Lijun Cheng; Xiaoxue Lin; Xuwei He; Xiaojian Ji; Chenxuan Yang; Yunhao Tang; Minzhi Yang; Zhisen Gao; et al. (Chemical Engineering Journal, 2024)

Molecular-level insight into the origin-dependent adsorption fractionation of dissolved organic matter on ferrihydrite in aquatic environment: Implications for carbon sink in eutrophic lakes - Chengyu Suo; Wensi Zhao; Shasha Liu; Rui Fu; Yi Ren; Yue Qiu; Yuxin Zhang; Zhongqi He; Baoshan Xing; Fengchang Wu (Chemical Engineering Journal, 2024)

Redistribution and activation of inert N-configuration in metallic electron donor towards boosted oxygen reaction kinetics for zinc-air batteries - Yiyao Cao; Yakai Chen; Ke Chen; Lingling Sun; Wenhao Si; Yan Yan; Huijuan Lin; Jixin Zhu; Peilei He; Yan Lu; Haijiao Xie; Kun Rui (Chemical Engineering Journal, 2024)

Mechanism of phenols evolution during pyrolysis of Shendong coal macerals swelled with oxygen-containing organic solvents: Experimental and DFT study - Linyang Wang; Qiuxiang Yao; Rui Cao; Lei He; Ming Sun; Xiaoxun Ma (Chemical Engineering Journal, 2024)

Controlling amine monomers via UiO-66-NH2 defect sites to enhance forward osmosis membrane performance for lithium recovery - Miaolu He; Weiting Zhang; Huihui Zhang; Jie Lian; Yunlong Gao; Jin Wang; Yongtao Lv; Xudong Wang; Rui Miao; Lei Wang (Chemical Engineering Journal, 2024)

Highly nanostructured and carboxylated wood aerogel-based adsorption membrane reconstructed by grafting of polyacrylic acid for efficient removal of heavy-metal ions - Wen He; Bairen Wei; Shuang Liang; Rui Wang; Qiulin Ji; Gangzheng Hu; Wenxuan Li; Lei He; Juan Yu; Hongfei Zhu; Kaiyin Wang (Chemical Engineering Journal, 2024)

Polydatin: a potential NAFLD therapeutic drug that regulates mitochondrial autophagy through SIRT3-FOXO3-BNIP3 and PINK1-PRKN mechanisms - a network pharmacology and experimental investigation - Jing He; Yi-cai Qian; Ying-chuan Yin; Jing-rui Kang; Tian-rong Pan (Chemico-Biological Interactions, 2024)

Interfacial exchange of airflow and bacteria-carrying particles induced by door opening and foot traffic in an operating room - Haiyang Liu; Zhijian Liu; Junzhou He; Chenxing Hu; Rui Rong (Building and Environment, 2024)

Adsorption retention of spiramycin in agricultural calcareous loess soils: Assessing the impact of influential factors and mechanisms - Zhewei Liu; Yufeng Jiang; Rui He; Jiali Wu; Xiaozhen Zhang; Kui Huang; Yingqin Wu (Water, Air, & Soil Pollution, 2024)

Prediction of solar activities: Sunspot numbers and solar magnetic synoptic maps - Rui Zhuo; Jiansen He; Die Duan; Rong Lin; Ziqi Wu; Limei Yan; Yong Wei (Science China Earth Sciences, 2024)

Calcitriol Inhibits NaAsO2 Triggered Hepatic Stellate Cells Activation and Extracellular Matrix Oversecretion by Activating Nrf2 Signaling Pathway Through Vitamin D Receptor - Dapeng Wang; Rui He; Qian Song; Heng Diao; Ying Jin; Aihua Zhang (Biological Trace Element Research, 2024)

Probing rotaxane dynamics with 19F NMR/MRI: Unveiling the roles of mechanical bond and steric hindrance - Yu Li; Man Luo; Mou Jiang; Rui Zhou; Wanrong Yang; Shenhui Li; Fang Wang; Lijun Zhu; Pei He; Minghui Yang; Xin Zhou; Zhong-Xing Jiang; et al. (Analytica Chimica Acta, 2024)

Genetic affinity of cave burial and Hmong-Mien populations in Guangxi inferred from ancient genomes - Jianxin Guo; Haifeng He; Guangmao Xie; Le Tao; Xi Mai; Kongyang Zhu; Qiusheng Qin; Xiaomin Yang; Ying Xie; Rui Wang; Hao Ma; Jing Zhao; et al. (Archaeological and Anthropological Sciences, 2024)

Recent advances and optimization strategies for the microbial degradation of PCBs: From monocultures to microbial consortia - Rui Chen; Ruolin Qin; He Bai; Xiaoqiang Jia (Critical Reviews in Environmental Science and Technology, 2024)

In situ acid production by organic matter induced with trace homogeneous Fenton reagent for membrane fouling control - Rui Miao; Haoxue Ran; Yifan Yang; Yanfei Li; Zhuowen Ma; Yongtao Lv; Xiaorong Meng; Miaolu He; Lei Wang (Water Research, 2024)

Comprehensive analysis of metal(loid)s and associated metal(loid) resistance genes in atmospheric particulate matter - Xiu-Peng Liang; He-Jing Wang; Jie-Ru Zheng; Xiao-Ru Wang; Dao-Ming Lin; Ya-Qing Wu; Rui-Lian Yu; Gong-Ren Hu; Yu Yan (Science of The Total Environment, 2024)

Sub-daily live fuel moisture content estimation from Himawari-8 data - Xingwen Quan; Rui Chen; Marta Yebra; David Riaño; Víctor Resco de Dios; Xing Li; Binbin He; Rachael H. Nolan; Anne Griebel; Matthias M. Boer; Yuanqi Sun (Remote Sensing of Environment, 2024)

Wastewater surveillance together with metaviromic data revealed the unusual resurgence of infectious diseases after the first wave of the COVID-19 outbreak - Ziqiang Zhang; Fenglan He; Liu Yi; Zhiqiang Deng; Rui Wang; Lixin Shen; Songzhe Fu (Journal of Hazardous Materials, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Electrochemiluminescence detection of diazinon in vegetables based on the synergistic interaction of WO3-x dots with Au@SiO2 nanocapsules - Wenzheng Liu; Haifang Wang; Peisen Li; Chengqiang Li; Donghan Li; Zhenying He; Yuhao Zhang; Jingcheng Huang; Jin Hua; Rui Xu; Lianming Xia; Yemin Guo; et al. (Food Chemistry, 2024)

The role of hormones in the regulation of lactogenic immunity in porcine and bovine species - Kexin Hua; Dan Liu; Qianshuai Xu; Yuna Peng; Yu Sun; Rongrong He; Rui Luo; Hui Jin (Domestic Animal Endocrinology, 2024)

Indentification of coal-origin structural units by multi-step pyrolysis through Py-GC/MS and by DFT calculation - Lei He; Qiuxiang Yao; Rui Cao; Linyang Wang; Wei Wang; Duo Ma; Ming Sun; Xiaoxun Ma (Chemical Engineering Journal, 2024)

A NIR-II quantum dot-assisted dual-color imaging strategy enables simultaneous tracking of two subtypes of extracellular vesicles in vivo - Xing-Chi Liu; He-Jing Zhang; Rui Xu; Jing Liu; Hou-Fu Xia; Qi-Hui Xie; Zhi-Quan Tian; Zi-Li Yu; Gang Chen (Chemical Engineering Journal, 2024)

The Association Between the Levels of Oxidative Stress Indicators (MDA, SOD, and GSH) in Seminal Plasma and the Risk of Idiopathic Oligo-asthenotera-tozoospermia: Does Cu or Se Level Alter the Association? - Tao Yin; Xinyu Yue; Qian Li; Xinyu Zhou; Rui Dong; Jiayi Chen; Runtao Zhang; Xin Wang; Shitao He; Tingting Jiang; Fangbiao Tao; Yunxia Cao; et al. (Biological Trace Element Research, 2024)

Calculations of solubilities of pure noble gases and He–CO2/CH4/N2 gas mixtures in aqueous solutions with accurate thermodynamic models - Sensen He; Rui Sun; Zhiyan Pan; Shaocong Lai (Applied Geochemistry, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

In-situ comprehensive investigation of deformation mechanism of the rock mass with weak interlayer zone in the Baihetan hydropower station - Jin-Shuai Zhao; Bing-Rui Chen; Quan Jiang; Ding-Ping Xu; Ben-Guo He; Shu-Qian Duan (Tunnelling and Underground Space Technology, 2024)

Corrigendum to “Silicon in soil and its interaction with nitrogen, phosphorus, and potassium nutrients on rice yield: A case study of paddy fields in the Taihu Lake region, China, without a history of silicon fertilization” [Soil Tillage Res. 238 (2024) 106027] - Sihua Huang; Lijie Pu; Gaili He; Xiaoqing Wang; Dejing Chen; Xuefeng Xie; Lu Qie; Yang Dan; Rui Zhang; Zhongshun Gong; Yumeng Lu (Soil and Tillage Research, 2024)

Cu-II-directed self-assembly of fullerenols to ameliorate copper stress in maize seedlings - Chenjie Fan; Qingyuan Liang; Yan Wang; Peimei Chen; Jiakai Wu; Qingnan Wu; Shijun Jiang; Yang Zhou; Rui He; Fuju Tai (Science of The Total Environment, 2024)

A new Late Devonian plant assemblage in West Junggar, Xinjiang, China and its floral evolution during the Devonian - Bing-Cai Liu; Kai Wang; Rui-Wen Zong; Jiao Bai; Yao Wang; Ning Yang; Yi Wang; Hong-He Xu (Review of Palaeobotany and Palynology, 2024)

Changes in the lithosphere, atmosphere, and ionosphere before and during the Mw = 7.7 Jamaica 2020 earthquake - Dedalo Marchetti; Kaiguang Zhu; Alessandro Piscini; Essam Ghamry; Xuhui Shen; Rui Yan; Xiaodan He; Ting Wang; Wenqi Chen; Jiami Wen; Yiqun Zhang; Yuqi Cheng; et al. (Remote Sensing of Environment, 2024)

Three new quinic acid derivatives and a new shikimic acid derivative from the leaves of Castanopsis orthacantha - Xue-Xue Cheng; Ya-Feng Wang; Rui-Jie He; Bing-Yuan Yang; Zhang-Bin Liu; Yong-Lin Huang (Phytochemistry Letters, 2024)

Model predictive control of wave energy converters - Ming Zhang; Shuang-Rui Yu; Guang-Wei Zhao; Sai-Shuai Dai; Fang He; Zhi-Ming Yuan (Ocean Engineering, 2024)

Carbon performance analysis of upgraded wastewater treatment plants in key control areas of the Ziya River Basin in China - Jiahao Liu; Zhongqian Wang; Tonggang Zhang; Rui Liu; Weiguang He; Xiangye Kong; Yaolong Shi; Jianfeng Xie (Journal of Environmental Management, 2024)

Synergistic effects of Co-pyrolysis on the immobilization and transformation of lead (Pb), chromium (Cr), nickel (Ni), and fluorine (F) in phosphogypsum-biomass mixtures - Minjie He; Rui Xu; Guangfei Qu; Xianyu Fu; Xinxin Liu; Hanghang Wang; Yaxin Tian; Chenyang Yin (Journal of Environmental Management, 2024)

Pyrite/biochar-activated peroxymonosulfate strengthens tetracycline degradation: Important roles of surface functional groups and Fe(Ⅱ)/Fe(Ⅲ) redox cycling - Jieru Fang; Fang He; Zelong Yan; Jingjing Wang; Rui Yu; Haihong Zhou (Journal of Environmental Chemical Engineering, 2024)

A synergistic polyelectrolytes-Zr-MOF hydrated construction graphene oxide nanofiltration with enhanced dye wastewater remediation - Lan Ma; Guilan Zhang; Yan Wan; Teng Wang; Xinyan Li; Yin Zhang; Tianfeng He; Rui Han; Liyun Zhang (Journal of Environmental Chemical Engineering, 2024)

High-pressure microfluidization enhanced the stability of sodium caseinate-EGCG complex-stabilized fish oil emulsion - Wei Tang; Rui Wang; Minghui Li; Qingchun Zhang; Jianfei He; Dan Liu; Yuqi Feng; Weilin Liu; Jianhua Liu (Food Chemistry, 2024)

A comparative evaluation of the structure, functionality and volatile profiles of Trichosanthes kirilowii seed protein isolates based on different extraction methods - Dong Peng; Zhilin He; Xiangmin Pan; Rui Zheng; Hanxiao Bao; Jingru Liao; Ling Dong; Weiwen Li; Jianping Chen; Pan Li; Bing Du (Food Chemistry, 2024)

Hydration properties and mesoscopic structures of different depolymerized konjac glucomannan: Experiments and molecular dynamics simulations - Yi Zhao; Juan Wang; Yuan Zhang; Rui He; Yuming Du; Geng Zhong (Food Hydrocolloids, 2024)

Effective and food-grade detoxification of multiple mycotoxins using yeast expressed manganese peroxidases - Yang You; Yangyu Qiu; Huidong Xu; Rui He; Lili Zhang; Zhouping Wang; Yu Xia (Food Bioscience, 2024)

Recent advances of 2D materials in capacitive deionization - Jun Jin; Wen Xi; Zongchang Li; Jianing Hu; Rui Wang; Yansheng Gong; Beibei He; Huanwen Wang; Youfang Zhang (Desalination, 2024)

Winkler spring coefficients for laterally loaded piles - Rui He; Amir M. Kaynia (Computers and Geotechnics, 2024)

Manipulating cationic ordering toward highly efficient and zero-thermal-quenching cyan photoluminescence - Hongzhi Zhang; Hong Li; Conglin Liu; Hongming Jiang; Junpeng Li; Yuxin Liu; Jiayi He; Rui Wang; Wanbiao Hu; Jing Zhu (Chemical Engineering Journal, 2024)

Highspeed transport pathway dominated by continuous arrangement of micron-sized hollow MOFs in MMMs to accelerate CO2 permeation - Wenji Zheng; Rui Ding; Ziheng Li; Xuehua Ruan; Yan Dai; Miao Yu; Xiangcun Li; Xiaoming Yan; Xiaobin Jiang; Xiujuan Zhang; Gaohong He (Chemical Engineering Journal, 2024)

Improved seed yield and phosphorus accumulation in soybean are associated with the enhanced root exudates in south-west China - Hong-Lan Zhang; Nian Liang; Rui Dong; Chang-An Liu; Chun-Ling Hao; Kadambot H. M. Siddique; Jin He (Plant and Soil, 2024)

Primary Cutaneous Mucormycosis Caused by Mucor irregularis in a Chinese Man - Zhihua Li; Qing Jiang; Xiaohua Tao; Zhenhua Zhang; Luhuai Shi; Lifang Cheng; Pingxiu He; Xinyi Fan; Rui Xu; Yunpeng Luo; Yangmin Gao (Mycopathologia, 2024)

Gold nanocluster-based ratiometric fluorescence immunoassay for broad-spectrum screening of five eugenols - Lin Luo; Zhen-Xi He; Bao-Zhu Jia; Rui-Yao Kang; Wen-Feng Zhang; Ri-Ming Huang; Zhen-Lin Xu (Analytica Chimica Acta, 2024)

Developing an evaluation system for green resin suppliers in the plastic toy industry based on collaboration willingness - Qiu-Rui He; Ping-Kuo Chen (Environment, Development and Sustainability, 2024)

A newly defined latest Carboniferous-Permian ridge subduction in the southern Altaids: Insights from adakitic, S-type, and I-type granitoids in the northern East Junggar (NW China) - Jingmin Gan; Wenjiao Xiao; Qigui Mao; Hao Wang; He Yang; Miao Sang; Xiaoliang Jia; Yin Liu; Zhiyong Zhang; Zhou Tan; Rui Li (International Geology Review, 2024)

Unlocking the potential of biochar: an iron-phosphorus-based composite modified adsorbent for adsorption of Pb(II) and Cd(II) in aqueous environments and response surface optimization of adsorption conditions - Xu Li; Yuan Chi; Feng Ma; Xiaoxin Wang; Rui Du; Zhipeng Wang; Xiaoyan Dang; Chaoyue Zhao; Yanping Zhang; Shumin He; Youzhao Wang; Tong Zhu (Environmental Science and Pollution Research, 2024)

Effect of sludge redistribution strategy on stability of partial nitrification-anammox process: Further exploration of the potential value of sludge - Peng Wang; Rui Ou; Jun Tan; Ning Li; Min Zheng; Qinghai Jin; Jin Yu; Di He (Chemosphere, 2024)

Morphological estimation of primary branch length of individual apple trees during the deciduous period in modern orchard based on PointNet++ - Xiaoming Sun; Leilei He; Hanhui Jiang; Rui Li; Wulan Mao; Dong Zhang; Yaqoob Majeed; Nikita Andriyanov; Vladimir Soloviev; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

Modeling the long-range transmission of airborne bioaerosol releases in a high-density urban environment - Zhijian Dong; Zhijian Liu; Chenxing Hu; Yongjun Jin; Chenglin Ye; Yuchen He; Rui Rong (Urban Climate, 2024)

Role and action mechanisms of miR-149 and miR-31 in regulating function of pig cumulus cells and oocytes - Jia-Shun Wu; Shuai Gong; Min Zhang; Rui-Jie Ma; Hui-Li Wang; Ming-Jiu Luo; Nan He; Jing-He Tan (Theriogenology, 2024)

Brittle sedimentary strata focus a multimodal depth distribution of seismicity during hydraulic fracturing in the Sichuan Basin, Southwest China - Mengke An; Derek Elsworth; Fengshou Zhang; Rui Huang; Junlun Li; Zhengyu Xu; Zhen Zhong; Manchao He (Tectonophysics, 2024)

Silicon in soil and its interaction with nitrogen, phosphorus, and potassium nutrients on rice yield: A case study of paddy fields in the Taihu Lake region, China, without a history of silicon fertilization - Sihua Huang; Lijie Pu; Gaili He; Xiaoqing Wang; Dejing Chen; Xuefeng Xie; Lu Qie; Yang Dan; Rui Zhang; Zhongshun Gong; Yumeng Lu (Soil and Tillage Research, 2024)

Anthropogenic-induced ecological risks on marine ecosystems indicated by characterizing emerging pollutants in Pearl River Estuary, China - He Liu; Bo Zhao; Meng Jin; Rui Wang; Zirong Ding; Xiong Wang; Wenjie Xu; Qianghua Chen; Rizhu Tao; Jianping Fu; Danping Xie (Science of The Total Environment, 2024)

Trends and drivers of Arctic-boreal fire intensity between 2003 and 2022 - Yanxi Li; Thomas A.J. Janssen; Rui Chen; Binbin He; Sander Veraverbeke (Science of The Total Environment, 2024)

A novel stress concentration inspection method for marine oil and gas pipeline based on UNSM - Jiaxing Xin; Jinzhong Chen; Renyang He; Rui Li; Xiaolong Li; Chang Liu; Run-kun Lu; Zhengda Su; Wenbo Han (Ocean Engineering, 2024)

Origin of a high-velocity layer: Insights from seismic reflection imaging (South China Sea) - Qing He; Zongdong Pan; Shaoping Lu; Hongfang Gao; Han Chen; Rui Gao (Marine and Petroleum Geology, 2024)

Insights into the generation of multiple reactive species in UV254/PMS/I− system and their roles for degradation of phenolic and non-phenolic pollutants - Zhen Tian; Yiyang Li; Lina Wang; Rui Xu; Aihua Wei; Jun He; Chengjun Wang (Journal of Water Process Engineering, 2024)

A novel aldo-keto reductase gene, OsAKR1, from rice confers higher tolerance to cadmium stress in rice by an in vivo reactive aldehyde detoxification - Rui Guo; Qiang Zhang; Chang Zhao Chen; Jie Ya Sun; Chun Yan Tu; Meng Xing He; Ren Fang Shen; Jiu Huang; Xiao Fang Zhu (Journal of Hazardous Materials, 2024)

Experimental study and model optimization of thermodynamic performance of a single screw water vapor compressor - Huafu Zhang; Zhentao Zhang; Lige Tong; Junling Yang; Yanan Li; Li Wang; Xia Guo; Rui Tian; Mingxin He; Chongguang Gao (International Journal of Refrigeration, 2024)

Comparative toxicology of algal cell extracts and pure cyanotoxins: insights into toxic effects and mechanisms of harmful cyanobacteria Raphidiopsis raciborskii - Zhongshi He; Youxin Chen; Jin Gao; Yewei Xu; Xinya Zhou; Rui Yang; Ruozhen Geng; Renhui Li; Gongliang Yu (Harmful Algae, 2024)

Temperature driven real-time weakening and strengthening mechanisms of unconfined granite - Fei Wang; Rui Pang; Heinz Konietzky; Ke Hu; Ben-Guo He; De-Hao Meng; Mohamed Ismael (Geothermics, 2024)

SERS detection of triazole pesticide residues on vegetables and fruits using Au decahedral nanoparticles - Zhinan Chen; Rui Tan; Mei Zeng; Xue Yuan; Kaiyi Zhuang; Changsheng Feng; Yi He; Xiaojun Luo (Food Chemistry, 2024)

Protein from rapeseed for food applications: Extraction, sensory quality, functional and nutritional properties - Rui Zhang; Xuelian Fang; Zisheng Feng; Ming Chen; Xiushuang Qiu; Jinmeng Sun; Muci Wu; Jingren He (Food Chemistry, 2024)

Relationship of solid fuels use with cognitive function and efficacy of switching to cleaner fuels or using ventilation: A systematic review and meta-analysis - Rui Yang; Jie He; Kang-kang Zhong; Ming-xuan Fan; Teng Bao; Xue-Chun Liu; Qi Zhong (Environmental Research, 2024)

Influence of microplastics and environmentally persistent free radicals on the ability of biochar components to promote degradation of antibiotics by activated peroxymonosulfate - Yanzhuo Zhang; Rui He; Yutai Sun; Jing Zhao; Xiaozhuan Zhang; Jiqin Wang; Alexandr V. Bildyukevich (Environmental Pollution, 2024)

Wearable active-cooling garment for personalized thermoregulation in vehicle - Rui Zhang; Zhi-Zhu He (Energy and Buildings, 2024)

Enhanced peroxymonosulfate activation for degradation of iodinated contrast media by microwave-induced bimetallic carbon-based catalysts: Insight into the synergistic mechanism between microwaves and bimetallic sites - Zixia He; Zhen Tian; Juan Luo; Shichang Sun; Guopeng Zhu; Rui Ma (Chemical Engineering Journal, 2024)

Refining granite generation by interrogation of zircon and monazite U-Th-Pb and Hf/Nd-O isotopes - Xing Zhang; Yuanbao Wu; Bin Fu; Wenxiang Zhang; Long Li; Guangyan Zhou; Rui Li; Zhaochu Hu; Yu He; Zhengwei Qin (Chemical Geology, 2024)

The influence of complex terrain on cloud and precipitation on the foot and slope of the southeastern Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Jian Li; Xiaoqing Wu; Xiaoqi Xu; Shiying Wu; Rui Hu; Xin He; Zhuangzhuang Zhou; et al. (Climate Dynamics, 2024)

Exquisite visualization of mitophagy and monitoring the increase of lysosomal micro-viscosity in mitophagy with an unusual pH-independent lysosomal rotor - Rui Yang; Wei He; Changxin Zhu; Xifeng Yang; Yawei Kuang; Tao Zhu; Jingyang Xu; Yuang Zhao; Tingwang Jiang; Yushen Liu; Mengmeng Wei (Analytica Chimica Acta, 2024)

CircRNA: a rising therapeutic strategy for lung injury induced by pulmonary toxicants - Cai Liao; Zhen-Wei He; Rui Yu; Ya-Jie Yu; Xiao-Ru Liu; De-Lei Kong; Yun Wang (Archives of Toxicology, 2024)

Triterpene hexahydroxydiphenoyl ester and phenol glucosides from the leaves of Castanopsis eyrie (Champ. ex Benth.) Hutch - Bing-Yuan Yang; Nao Pang; Rui-Jie He; Ya-Feng Wang; Yong-Lin Huang (Natural Product Research, 2024)

ARHGEF18 can promote BVDV NS5B activation of the host NF-κB signaling pathway by combining with the NS5B-palm domain - Jiying Yin; Naichao Diao; Tian Tian; Qi Wang; Shuqi Ma; Ning He; Hongming Zhou; Zehui Zhou; Wenyi Jia; Xiaonan Wang; Kun Shi; Rui Du (Veterinary Microbiology, 2024)

Corrigendum to “Horizontal transfer of antibiotic resistance genes within the bacterial communities in aquacultural environment” [Sci. Total Environ. 820 (2022) 153286] - Songzhe Fu; Qingyao Wang; Rui Wang; Yixiang Zhang; Ruiting Lan; Fenglan He; Qian Yang (Science of The Total Environment, 2024)

Mitigation mechanism of ultrafiltration membrane fouling by Fe2+ with hydrogen peroxide for protein-rich wastewater treatment - Rui Miao; Chengshu Yang; Yue Mi; Jiani Qu; Yanfei Li; Yongtao Lv; Miaolu He; Lei Wang (Journal of Water Process Engineering, 2024)

Investigation of pathogen-laden aerosol aerodynamics and ventilation rates on their long-range transmission: A study on the Fangcang shelter hospital - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Shiyue Li; Rui Rong; Zhenyu Liang; Haiyang Liu; Jingwei Liu; Tongliang Wan; Junzhou He (Journal of Cleaner Production, 2024)

Afforestation enhances glomalin-related soil protein content but decreases its contribution to soil organic carbon in a subtropical karst area - Rui Gu; Kongcao Xiao; Zihong Zhu; Xunyang He; Dejun Li (Journal of Environmental Management, 2024)

Apparent isotope effects of reversible enzymatic reactions - Yuyang He; Martin Thullner; Rui Qin (Geochimica et Cosmochimica Acta, 2024)

Enhancing compound confidence in suspect and non-target screening through machine learning-based retention time prediction - Dehao Song; Ting Tang; Rui Wang; He Liu; Danping Xie; Bo Zhao; Zhi Dang; Guining Lu (Environmental Pollution, 2024)

Molten salt etching synthesis of Ti3C2Tx/Ni composites for highly efficient capacitive deionization - Wen Xi; Tianzhuo Guo; Zeren Xie; Youfang Zhang; Rui Wang; Yansheng Gong; Beibei He; Huanwen Wang; Jun Jin (Desalination, 2024)

Deformation and rupture of Janus nanoparticle-stabilized Pickering emulsion in confined channel - Yuanhao Chang; Senbo Xiao; Rui Ma; Zhiliang Zhang; Fanhua Zeng; Jianying He (Chemical Engineering Journal, 2024)

Microplastics provide new hotspots for frequent transmission of antibiotic resistance genes during anaerobic digestion of sludge containing antibiotics - Yinping Xiang; Weiping Xiong; Zhaohui Yang; Rui Xu; Yanru Zhang; Meiying Jia; Haihao Peng; Lele He; Chengyun Zhou (Chemical Engineering Journal, 2024)

Enhancing copper recycling through synergistic valence conversions in MnOx-modified capacitive deionization electrodes - Lujie Nie; Lei Wang; Xudong Wang; Miaolu He; Jin Wang; Yongtao Lv; Rui Miao; jiajun An; Jiajin Hao; Jiaqi Wang; Yanna Ren (Chemical Engineering Journal, 2024)

Correlation and interaction between urinary metals level and diabetes: A cross sectional study of community-dwelling elderly - Rui Wang; Pei He; Siyu Duan; Zhongyuan Zhang; Yuqing Dai; Meiyan Li; Zhuoheng Shen; Xiaoyu Li; Yanan Song; Yiping Sun; Rui Zhang; Jian Sun; et al. (Exposure and Health, 2024)

Initial and comprehensive analysis of PPP time transfer based on Galileo high accuracy service - Runzhi Zhang; Rui Tu; Xiaochun Lu; Zaimin He; Wei Guang; Gongwei Xiao (GPS Solutions, 2024)

Endothelial specific prolyl hydroxylase domain-containing protein 2 deficiency attenuates aging-related obesity and exercise intolerance - Lihong Pan; Xiaochen He; Rui Xu; Umesh Bhattarai; Ziru Niu; Jussara do Carmo; Yuxiang Sun; Heng Zeng; John S. Clemmer; Jian-Xiong Chen; Yingjie Chen (GeroScience, 2024)
Obesity and exercise intolerance greatly reduce the life quality of older people. Prolyl hydroxylase domain-containing protein 2 (PHD2) is an important enzyme in modulating hypoxia-inducible factor-alpha (HIF) protein. Using vascular endothelial cell-specific PHD2 gene knockout (PHD2 ECKO) mice, we investigated the role of endothelial PHD2 in aging-related obesity and exercise capacity. Briefly, PHD2 ECKO mice were obtained by crossing PHD2-floxed mice with VE-Cadherin (Cdh5)-Cre transgenic mice. The effect of PHD2 ECKO on obesity and exercise capacity in PHD2 ECKO mice and control PHD2 f/f mice were determined in young mice (6 to 7 months) and aged mice (16–18 months). We found that aged PHD2 ECKO mice, but not young mice, exhibited a lean phenotype, characterized by lower fat mass, and its ratio to lean weight, body weight, or tibial length, while their food uptake was not reduced compared with controls. Moreover, as compared with aged control mice, aged PHD2 ECKO mice exhibited increased oxygen consumption at rest and during exercise, and the maximum rate of oxygen consumption (VO 2 max) during exercise. Furthermore, as compared with corresponding control mice, both young and aged PHD2 ECKO mice demonstrated improved glucose tolerance and lower insulin resistance. Together, these data demonstrate that inhibition of vascular endothelial PHD2 signaling significantly attenuates aging-related obesity, exercise intolerance, and glucose intolerance.

Microplastics affect mosquito from aquatic to terrestrial lifestyles and are transferred to mammals through mosquito bites - Jian-hang Li; Xiao-hui Liu; Guo-rui Liang; He-ting Gao; Si-han Guo; Xin-yu Zhou; Dan Xing; Teng Zhao; Chun-xiao Li (Science of The Total Environment, 2024)

Cement kiln geared up to dispose industrial hazardous wastes of megacity under industrial symbiosis - Kailingli Liao; Zeshi Feng; Jin Wu; He Liang; Yuhan Wang; Wenfei Zeng; Yichun Wang; Jinping Tian; Rui Liu; Lyujun Chen (Resources, Conservation and Recycling, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

Quantitative health risk assessment of microbial hazards from water sources for community and self-supply drinking water systems - Cheng Yan; Wei-di Wan; Rui-ning Wang; Tian-nuo Lai; Wajid Ali; Shan-shan He; Sai Liu; Xiang Li; Zaheer Ahmad Nasir; Frederic Coulon (Journal of Hazardous Materials, 2024)

A quantitative model to estimate major oxide abundances on the Moon based on in situ reflectance spectral data of Chang'e missions - Zhenxing Zhao; Yazhou Yang; Xing Wu; Yang Liu; Feng Zhang; Rui Xu; Zhiping He; Yangting Lin; Yongliao Zou (Icarus, 2024)

The pH adjustment of Vitis amurensis dry red wine revealed the evolution of organic acids, volatomics, and sensory quality during winemaking - Meng-Bo Tian; Rui-Qi Hu; Zhao-Long Liu; Ning Shi; Hao-Cheng Lu; Chang-Qing Duan; Jun Wang; Yan-Feng Sun; Qing-Sen Kong; Fei He (Food Chemistry, 2024)

Innovative multistep modifications of β-Lactoglobulin for enhanced emulsifying and antioxidant activities - Qingchun Zhang; Rui Wang; Jianfei He; Wei Tang; Jianhua Liu (Food Hydrocolloids, 2024)

Structural design of La2(CO3)3 loaded magnetic biochar for selective removal of phosphorus from wastewater - Erming Ouyang; Hanrui Xiang; Rui Zhao; Hongwei Yang; Wanyuan He; Ruiyue Zhang (Environmental Pollution, 2024)

Effects of environmental and nutritional labels on the dietary choices of consumers: Evidence from China - Xue Sun; Rui Wang; Pan He; Beibei Liu (Environmental Impact Assessment Review, 2024)

Thermo-mechanical Coupling Characteristics of Granite under Triaxial Pressures and Ultrahigh Heating Rates - Fei Wang; Dehao Meng; Ke Hu; Xun Du; Rui Pang; Yanlin Zou; Wengang Dang; Benguo He (Computers and Geotechnics, 2024)

Scrub-vegetation cover impact on soil water migration and temperature change during freeze–thaw events in sandy desert soils of northwest China - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Ruiting Jia (CATENA, 2024)

Evaluation of CO2 and NOx emissions from container diesel trucks using a portable emissions measurement system - Hong-mei Zhao; Hong-di He; Dan-ni Lu; Dai Zhou; Chun-xia Lu; Xiao-rui Fang; Zhong-ren Peng (Building and Environment, 2024)

Controlling airborne pathogen within Fangcang shelter hospitals: Aerodynamic analysis of bioaerosols released from various locations through experiment and simulation - Chuan Jiang; Zhijian Liu; Xia Xiao; Haiyang Liu; Junzhou He; Rui Rong; Jingwei Liu; Zhenzhe Huang; Yongxin Wang (Building and Environment, 2024)

Genetic lineage tracing identifies adaptive mechanisms of pancreatic islet β cells in various mouse models of diabetes with distinct age of initiation - Qi Fu; Yu Qian; Hemin Jiang; Yunqiang He; Hao Dai; Yang Chen; Zhiqing Xia; Yucheng Liang; Yuncai Zhou; Rui Gao; Shuai Zheng; Hui Lv; et al. (Science China Life Sciences, 2024)

Influence of Lithology on the Stability of Organic Carbon in Typical Soils of Karst in Northwest China - Lening Hu; Liming Zhou; Rui Qin; Hua Deng; Jianing Zhang; Yuefeng Yu; Tieguang He (Journal of Soil Science and Plant Nutrition, 2024)

RNAi-mediated plant sterol modification to control insect herbivore pests: insights from Arabidopsis and the diamondback moth - Ivy W. Chen; Robert J. Grebenok; Cheng Zhao; Li He; Jiaxin Lei; Rui Ji; Nicolo Hernandez; Joshua S. Yuan; Hisashi Koiwa; Spencer T. Behmer; Keyan Zhu-Salzman (Journal of Pest Science, 2024)

Sources and transformation of nitrate in an agricultural riverine reservoir watershed of the Sichuan Basin - Fen Xu; Kexin He; Hong Wang; Xiaoxia He; Yaqian Zhou; Jie Qin; Lishan Wu; Rui Yang; Jianfei Yuan (Applied Geochemistry, 2024)

Drought-related wildfire accounts for one-third of the forest wildfires in subtropical China - Jianpeng Yin; Binbin He; Chunquan Fan; Rui Chen; Hongguo Zhang; Yiru Zhang (Agricultural and Forest Meteorology, 2024)

Bisphenol A affects microbial interactions and metabolic responses in sludge anaerobic digestion - Xiao He; Yinping Xiang; Rui Xu; Hanbing Gao; Zhaohui Guo; Weimin Sun (Environmental Science and Pollution Research, 2024)

Improved binocular localization of kiwifruit in orchard based on fruit and calyx detection using YOLOv5x for robotic picking - Changqing Gao; Hanhui Jiang; Xiaojuan Liu; Haihong Li; Zhenchao Wu; Xiaoming Sun; Leilei He; Wulan Mao; Yaqoob Majeed; Rui Li; Longsheng Fu (Computers and Electronics in Agriculture, 2024)

Cotton Verticillium wilt monitoring based on UAV multispectral-visible multi-source feature fusion - Rui Ma; Nannan Zhang; Xiao Zhang; Tiecheng Bai; Xintao Yuan; Hao Bao; Daidi He; Wujun Sun; Yong He (Computers and Electronics in Agriculture, 2024)

The immune response of Caspase-3 gene in infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection of Litopenaeus vannamei - Cai-Yi Chen; Ning Yang; Chuanyu He; Yang Gao; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan (Aquaculture, 2024)

Mathematical optimization of waste management systems: Methodological review and perspectives for application - Mexitli Sandoval-Reyes; Rui He; Rui Semeano; Paulo Ferrão (Waste Management, 2024)

A particle-scale insight into the face stability of shallow EPB shield tunnels in dry cobble-rich soil - Jun Wang; Guojin Lin; Rui Tang; Yan Zhang; Zhigang Yao; Kun Feng; Ning Tian; Ziquan Chen; Chuan He (Tunnelling and Underground Space Technology, 2024)

Failure mechanism of rock masses with complex geological conditions in a large underground cavern: A case study - Jin-Shuai Zhao; Shu-Qian Duan; Bing-Rui Chen; Lei Li; Ben-Guo He; Peng-Xiang Li; Guo-Feng Liu (Soil Dynamics and Earthquake Engineering, 2024)

Reproducibility in nontarget screening (NTS) of environmental emerging contaminants: Assessing different HLB SPE cartridges and instruments - Wenhao Jia; He Liu; Yini Ma; Guolong Huang; Yaxiong Liu; Bo Zhao; Danping Xie; Kaibo Huang; Rui Wang (Science of The Total Environment, 2024)

Targeted amplicon sequencing facilitated a novel risk assessment framework for assessing the prevalence of broad spectrum bacterial and coronavirus diseases - Songzhe Fu; Haifeng Li; Fenglan He; Rui Wang; Yixiang Zhang; Ziqiang Zhang; Hui Li (Science of The Total Environment, 2024)

Impacts of re-vegetation on soil water dynamics in a semiarid region of Northwest China - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li (Science of The Total Environment, 2024)

Structurally diverse rearranged sesquiterpenoids, including a pair of rare tautomers, from the aerial parts of Daphne penicillata - Peng Zhao; Ben-Song Xin; Li Ye; Zhen-Tao Ma; Guo-Dong Yao; Rui Shi; Xia-Hong He; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Investigation of the intrinsic characteristics of two lock-in regions in a 10:1 π-shaped deck - Jiaying Wang; Feng Wang; Rui He; Jiawu Li; Jianming Hao; Jiupeng Zhang; Xiaoming Huang (Ocean Engineering, 2024)

CO2 storage capacity estimation by considering CO2 Dissolution: A case study in a depleted gas Reservoir, China - Youwei He; Mengyun Liu; Yong Tang; Cunqi Jia; Yong Wang; Zhenhua Rui (Journal of Hydrology, 2024)

Quantifying the agglomeration effect of reclaimed asphalt pavement on performance of recycled hot mix asphalt - Junxi He; Yuetan Ma; Kunpeng Zheng; Zhiqiang Cheng; Shengjia Xie; Rui Xiao; Baoshan Huang (Journal of Cleaner Production, 2024)

Estimation of potential wildfire behavior characteristics to assess wildfire danger in southwest China using deep learning schemes - Rui Chen; Binbin He; Yanxi Li; Chunquan Fan; Jianpeng Yin; Hongguo Zhang; Yiru Zhang (Journal of Environmental Management, 2024)

Change of soil bacterial communities in chemically stabilized chromium contaminated soils in an accelerated aging experiment - Linying Yao; Yuning He; Peng Zhao; Zhihao Xie; Longfei Jiang; Danni Li; Yueqiao Liu; Rui Ma; Jianli Jia; Dayi Zhang (Journal of Environmental Chemical Engineering, 2024)

Hierarchical porous UiO-66 composites modified by dual competitive strategy for adsorption of oxytetracycline - Tao He; Yi Wang; Rui Han; Xiaodong Li; Shihai Cui; Jing Yang (Journal of Environmental Chemical Engineering, 2024)

Fabrication of three-dimension hierarchical structure CuO nanoflowers and their antifungal mechanism against Bipolaris sorokiniana - Tenglong Xie; Jiaxiang Wang; Shibo Zhang; Jinhui Song; Guangtao Zan; Jiakai Wu; Risong Na; Qingnan Wu; Rui He (International Journal of Food Microbiology, 2024)

Mechanistic analysis of chemical structure evolution for coals under igneous intrusion - Shike Li; Yanming Zhu; Rui He (Fuel, 2024)

Characterization of the quasi-liquid layer on gas hydrates with molecular dynamics simulations - Yifan Zhang; Senbo Xiao; Rui Ma; Zhiliang Zhang; Jianying He (Fuel, 2024)

Palaeoenvironment characteristics of the Ediacaran Doushantuo Shale, Yichang area, South China: Implications for organic matter accumulation mechanism - Wei Yang; Sheng He; Zhongrui Wu; Gangyi Zhai; Rui Chen; Zijie Ning; Hongfei Lai; Jinfeng Ren; Chenlu Xu (Fuel, 2024)

Orange-spotted grouper IFNh response to NNV or MSRV and its potential antiviral activities - Siyou Huang; Rui Zheng; Yiling Kang; Linwei Yang; Jie Gao; Qingqing Liu; Shaoping Weng; Jianguo He; Junfeng Xie (Fish & Shellfish Immunology, 2024)

Involvement of TLRs/NF-κB/ESE-1 signaling pathway in T-2 toxin-induced cartilage matrix degradation - Yawen Shi; Rui Wang; Yanan Li; Yixin Cui; Ying He; Hui Wang; Yinan Liu; Meng Zhang; Yonghui Chen; Mingzhao Jia; Kunpan Chen; Xingran Ruan; et al. (Environmental Pollution, 2024)

Estimation of water quality variables based on machine learning model and cluster analysis-based empirical model using multi-source remote sensing data in inland reservoirs, South China - Di Tian; Xinfeng Zhao; Lei Gao; Zuobing Liang; Zaizhi Yang; Pengcheng Zhang; Qirui Wu; Kun Ren; Rui Li; Chenchen Yang; Shaoheng Li; Meng Wang; et al. (Environmental Pollution, 2024)

The occurrence of pollutants in organisms and water of inland mariculture systems: Shrimp aquaculture is a procession of Microplastics accumulation - Kexin Song; Siqi Xie; Changwen Li; Jincheng He; Wei Jin; Rui Wang; Wei Huang; Pingjing Li; Zhihua Feng (Environmental Pollution, 2024)

Complexities of regulating climate by promoting marine primary production with ocean iron fertilization - Hai-Bo Jiang; David A. Hutchins; Hao-Ran Zhang; Yuan-Yuan Feng; Rui-Feng Zhang; Wei-Wei Sun; Wentao Ma; Yan Bai; Mark Wells; Ding He; Nianzhi Jiao; Yuntao Wang; et al. (Earth-Science Reviews, 2024)

Rational construction of MOF-on-MOF heterojunction with an array of flexible two-dimensional microsheets for efficient CO2 photoreduction - Bing He; Ying-Jie Wang; Xuefeng Bai; He Bian; Yabo Xie; Rui Li; Jian-Rong Li (Chemical Engineering Journal, 2024)

Function-oriented bifunctional Mg & MoP modified polymeric carbon nitride for selective photoreduction CO2 to CH4 - Jun-ying Tang; Wei-guo Pan; Yu-lian He; Tian-shuo Zhao; Qing-shan Wang; Rui-tang Guo (Chemical Engineering Journal, 2024)

Effects of excess sludge composting process, environmentally persistent free radicals, and microplastics on antibiotics degradation efficiency of aging biochar - Yanzhuo Zhang; Yutai Sun; Rui He; Jing Zhao; Jiqin Wang; Tonghuan Yu; Xiaozhuan Zhang; Alexandr V. Bildyukevich (Bioresource Technology, 2024)

Calcineurin B-like protein ZmCBL8-1 promotes salt stress resistance in Arabidopsis - Ruilin Wang; Peimei Chen; Minglei Han; Wei Wang; Xiuli Hu; Rui He; Fuju Tai (Planta, 2024)

Evaluation of the performance of the latest WRF model (V4.5) in simulating surface elements and its sensitivity to the diurnal SST cycle in the South China Sea - Rui Shi; Ju Chen; Yunkai He; Wei Song; Daning Li; Yeqiang Shu; Dongxiao Wang (Climate Dynamics, 2024)

Molecular characterization of a novel mycovirus from binucleate Rhizoctonia AG-A strain A46 - Rui Shi; Xiaohan Mo; Zebin Chen; Wurong Chen; Shuhui Yu; He Liu; Yuchuan Li; Lili Dai; Yanqiong Li (Archives of Virology, 2024)

Distribution Characteristics and Factors Controlling Different Phosphorus Fractions in the Soils and Sediments of an Inland Lagoon - Kun Yuan; Rui Wang; Bo He; Guowei Fu; Yanwei Song; Lixin Pei; Shichao Fan; Fangyi Gao (Journal of Marine Science and Engineering, 2024)
Lagoons, significant coastal wetlands, stand out for their vital role in the cycles and transformations of phosphorus. However, the relationship between the spatial distributions of various phosphorus forms in the soil and sediments of lagoon areas remains unclear. This study investigated the phosphorus fractions and distribution patterns in the soil and sediments from Shimei Inland Sea, Hainan Province, China, and identified the factors controlling phosphorus distribution and its relationship with lagoon eutrophication. The results revealed significant enrichment of inorganic phosphorus (IP) in the Shimei Inland Sea (64.1–679.0 mg/kg) and offshore areas (56–627.2 mg/kg), while organic phosphorus (OP) was relatively concentrated in land (60–744.3 mg/kg), suggesting that the productivity of the terrestrial ecosystem controlled the OP content and IP formed from the mineralization of OP was more likely to leach into the water and combine with minerals. Total phosphorus (TP) content was negatively affected by pH, and organic matter, cation exchange capacity and iron/aluminum oxides showed significant positive correlations with TP content. These findings highlighted the coupled impact of soil and sediment physicochemical properties on phosphorus enrichment and transformation, providing theoretical support for the ecological restoration of ecosystems in tropical coastal wetlands.

3D-based precise evaluation pipeline for maize ear rot using multi-view stereo reconstruction and point cloud semantic segmentation - Rui Yang; Yong He; Xiangyu Lu; Yiying Zhao; Yanmei Li; Yinhui Yang; Wenwen Kong; Fei Liu (Computers and Electronics in Agriculture, 2024)

Vegetation-cover control of between-site soil temperature evolution in a sandy desertland - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Yalu Han; Shuang Feng; Lin Miao; Chen Liu (Science of The Total Environment, 2024)

Assessment for the data processing performance of non-target screening analysis based on high-resolution mass spectrometry - He Liu; Rui Wang; Bo Zhao; Danping Xie (Science of The Total Environment, 2024)

Soil phosphorus availability mediates the effects of nitrogen addition on community- and species-level phosphorus-acquisition strategies in alpine grasslands - Zhen-Huan Guan; Zuonan Cao; Xiao Gang Li; Thomas Scholten; Peter Kühn; Lin Wang; Rui-Peng Yu; Jin-Sheng He (Science of The Total Environment, 2024)

Forager-farmer transition at the crossroads of East and Southeast Asia 4900 years ago - Minmin Ma; Minxia Lu; Rui Sun; Zhonghua Zhu; Dorian Q. Fuller; Jianxin Guo; Guanglin He; Xiaomin Yang; Lingling Tan; Yongxiu Lu; Jiajia Dong; Ruiliang Liu; et al. (Science Bulletin, 2024)

Evolution of Silurian phytogeography, with the first report of Aberlemnia (Rhyniopsida) from the Pridoli of West Junggar, Xinjiang, China - Bing-Cai Liu; Rui-Wen Zong; Kai Wang; Jiao Bai; Yi Wang; Hong-He Xu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

LED-driven photocatalytic degradation of tetracycline by chromite ore processing residue (COPR): Mechanism, pathway, toxicity assessment - Shuo Zhang; Cunfang Lu; Yelei Wang; Cheng Tian; Peng Chen; Mingyuan Yang; Min Zhang; Rui Xu; Yuanyuan He; Zilong Li (Journal of Cleaner Production, 2024)

Fluid evolution and gas enrichment in the Wufeng-Longmaxi shale reservoirs of the eastern Sichuan Basin, SW China - Tao Luo; Xiaowen Guo; Zhiliang He; Tian Dong; Ze Tao; Rui Yang; Keqing Wang (Journal of Asian Earth Sciences, 2024)

Research progress on the construction of oxygen vacancy defects and application in photocatalytic oxidation of elemental mercury - Xin Yang; Zijian Xiang; Jiang Wu; Ping He; Yongfeng Qi; Shuo Chen; Yizheng Lu; Rui Xie; Zhengyu Liu; Chuman He (Fuel, 2024)

L.acidophilus participates in intestinal inflammation induced by PM2.5 through affecting the Treg/Th17 balance - Jie Xu; Jing Wang; Yuefeng He; Rui Chen; Qingtao Meng (Environmental Pollution, 2024)

Carbon monoxide-based immunogenic cell death amplifier remodels the hypoxic microenvironment for tumor sono-immunotherapy - Qian Wang; Zongyan He; Rui Zhang; Jun Du; Lejin Zhu; Xueyu Li; Han Yang; Yuqing Miao; Yuhao Li (Chemical Engineering Journal, 2024)

Photocatalytic degradation of benzotriazole through synergy of electron donor–acceptor units and Au clusters in covalent organic frameworks - Hui Wang; Yuhan Xiong; Yi He; Lingru Kong; Lan Ding; Rui Wu; Xin-Lei Gao; Jie Ding; Nanqi Ren (Chemical Engineering Journal, 2024)

1,4-Dioxane intervention enables simultaneous valorization of biomass-based C5 and C6 sugars to furfural over Hβ zeolite - Yujia He; Rui Zhang; Weipeng Song; Huai Liu; Junhua Zhang; Wenlong Jia; Lincai Peng (Chemical Engineering Journal, 2024)

Fischer-Tropsch synthesis to α-Olefins with low CO2 selectivity on a Co2C catalyst - Yiwen Liu; Chengyang He; Xingmao Jiang; Rui Zhang; Xinying Liu; Diane Hildebrandt; Xiaojun Lu (Chemical Engineering Journal, 2024)

Amino sugars influence Aspergillus fumigatus cell wall polysaccharide biosynthesis, and biofilm formation through interfering galactosaminogalactan deacetylation - Rui He; Pingzhen Wei; Arome Solomon Odiba; Linlu Gao; Sayed Usman; Xiufang Gong; Bin Wang; Linqi Wang; Cheng Jin; Guangtao Lu; Wenxia Fang (Carbohydrate Polymers, 2024)

Carbamazepine facilitated horizontal transfer of antibiotic resistance genes by enhancing microbial communication and aggregation - Yinping Xiang; Meiying Jia; Rui Xu; Jialu Xu; Lele He; Haihao Peng; Weimin Sun; Dongbo Wang; Weiping Xiong; Zhaohui Yang (Bioresource Technology, 2024)

Plasma membrane-localized hexose transporter OsSWEET1b, affects sugar metabolism and leaf senescence - Qiang Zhang; Changzhao Chen; Rui Guo; Xiaofang Zhu; Xinyu Tao; Mengxing He; Zhiwen Li; Lan Shen; Qing Li; Deyong Ren; Jiang Hu; Li Zhu; et al. (Plant Cell Reports, 2024)

Mechanism of Antidepressant Action of (2R,6R)-6-Hydroxynorketamine (HNK) and Its Compounds: Insights from Proteomic Analysis - Chaohui Zhen; Chong Wang; Yanjun Ma; Yuli Pang; Feiyue Cai; Jiali Meng; Yuefei He; Ping Xiao; Jianxi Liu; Xi Mei; Shupeng Li; Guanzheng Wu; et al. (Molecular Neurobiology, 2024)

Estimating the complete in-situ stress tensor along deep tunnels with frequent rockbursts near a steep valley - Ben-Guo He; Hong-Pu Li; Xia-Ting Feng; Xiang-Rui Meng (Bulletin of Engineering Geology and the Environment, 2024)

Effects of nutrients and light in aquatic habitat on the growth of Hydrocotyle vulgaris when expanded from terrestrial to aquatic habitat - Zhi-Huan Chen; Rui Zhang; Jun-Cai Xin; Zi-Han Qian; Shu-Jie Wang; Shang-Yan Qiu; Xue-Ge He; Chao Si (Aquatic Botany, 2024)

Evaluation on 131I production based on molten salt reactor off-gas extraction - Liang Chen; Liao-Yuan He; Bo Zhou; Gui-Feng Zhu; Yu-Han Fan; Hong-Jie Xu; Rui Yan; Yang Zou (Annals of Nuclear Energy, 2024)

Sympatric munias in tropical areas segregate spatially through different nest site selections to achieve coexistence - Chen-Wei Guo; Li-Li Li; Chen-Yang Liu; Ru-Chuan He; Rui-Chang Quan (Acta Oecologica, 2024)

Climate warming could free cold‐adapted trees from C‐conservative allocation strategy of storage over growth - Quan Zhou; Hang Shi; Rui He; Haikun Liu; Wenting Zhu; Shengjun Wu; Quanfa Zhang; Haishan Dang (Global Change Biology, 2024)
Carbon allocation has been fundamental for long‐lived trees to survive cold stress at their upper elevation range limit. Although carbon allocation between non‐structural carbohydrate (NSC) storage and structural growth is well‐documented, it still remains unclear how ongoing climate warming influences these processes, particularly whether these two processes will shift in parallel or respond divergently to warming. Using a combination of an in situ downward‐transplant warming experiment and an ex situ chamber warming treatment, we investigated how subalpine fir trees at their upper elevation limit coordinated carbon allocation priority among different sinks (e.g., NSC storage and structural growth) at whole‐tree level in response to elevated temperature. We found that transplanted individuals from the upper elevation limit to lower elevations generally induced an increase in specific leaf area, but there was no detected evidence of warming effect on leaf‐level saturated photosynthetic rates. Additionally, our results challenged the expectation that climate warming will accelerate structural carbon accumulation while maintaining NSC constant. Instead, individuals favored allocating available carbon to NSC storage over structural growth after 1 year of warming, despite the amplification in total biomass encouraged by both in situ and ex situ experimental warming. Unexpectedly, continued warming drove a regime shift in carbon allocation priority, which was manifested in the increase of NSC storage in synchrony to structural growth enhancement. These findings imply that climate warming would release trees at their cold edge from C‐conservative allocation strategy of storage over structural growth. Thus, understanding the strategical regulation of the carbon allocation priority and the distinctive function of carbon sink components is of great implication for predicting tree fate in the future climate warming.